2019
DOI: 10.1002/ese3.471
|View full text |Cite
|
Sign up to set email alerts
|

Application of flue‐gas foam in thermal‐chemical flooding for medium‐depth heavy oil reservoirs

Abstract: Heat loss in wellbore during steam injection is considerable due to the deep burial of medium‐depth heavy oil reservoirs, leading to a low steam quality in the bottom of well. As for hot water flooding, the mobility ratio between oil and water is small, which decreases oil recovery. Flue‐gas foam assisted thermal‐chemical flooding is a new method for heavy oil reservoir. Compared to hot water flooding, flue‐gas foam assisted thermal‐chemical flooding can decrease oil viscosity, achieving higher sweep efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Recently, there have been a number of examples of branched polymers being used to modify viscosities in lubricant and heavy oil applications, including transportation [35][36][37][38][39]. However, polymer addition has been reported to lead to a reduction in oil/lubricant quality [40,41]. In this respect, the importance of the oil solubility of these polymers has been shown to be important in minimising these issues and also improving traditional additives [42].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been a number of examples of branched polymers being used to modify viscosities in lubricant and heavy oil applications, including transportation [35][36][37][38][39]. However, polymer addition has been reported to lead to a reduction in oil/lubricant quality [40,41]. In this respect, the importance of the oil solubility of these polymers has been shown to be important in minimising these issues and also improving traditional additives [42].…”
Section: Introductionmentioning
confidence: 99%
“…8 Wang et al carried out physical simulation experiments to prove that the flue gas foam-assisted steam flooding technology had a good ability to improve the recovery of steam flooding. 9,10 It is well-known that the foam thermal stability is the key problem in steam flooding to improve the sweep efficiency. In general, the polymer has been widely used for foam stabilizers to improve the foam stability.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the foam also has the selective blocking characteristics, which can block the big pores rather than the small pores and block the water layers rather than the oil layers. , It is indicated that the foam is an ideal high-temperature profile control and flooding agent, and thus, foam is widely used in steam flooding for improving heavy oil recovery. , The experimental results by Bagheri and Clark showed that foam-assisted steam flooding could achieve good results, which verified the application prospect of foam-assisted steam flooding in the Canadian thermal recovery project being developed in northwest Alberta . Wang et al carried out physical simulation experiments to prove that the flue gas foam-assisted steam flooding technology had a good ability to improve the recovery of steam flooding. , …”
Section: Introductionmentioning
confidence: 99%
“…The main mechanisms of steam flooding include reducing the viscosity of crude oil, steam distillation, thermal expansion of crude oil, and steam drive (Fan et al, 2019). Currently, steam flooding is a large-scale industrial application of thermal recovery technology, which is an effective method to increase the oil recovery factor after CSS with achieved results (Dong et al, 2019;Du et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%